STATE-OF-THE-ART LIGHT WEIGHT BIOCOMPOSITE HELMETS FOR CHILDREN - V. M. Mathapati; A. B. Mugali; V. S. Umarani; S. K. Chougula; A. S. Reddy (International Journal of Innovations in Engineering Research and Technology, 2021)
Children start crawling normally at the age of 7-8 months and they learn walking stably by 2-3 years. However during this course of time many times they fall down and get head injuries. For the parents it is serious matter of concern and worries. Many varieties of head covers or helmets for children have beendeveloped and sold commercially. However they are costly, heavy and cause irritation and head itch. Therefore in the present work an attempt is made to design and develop a novel light weight biocomposite helmets for children. Simple hand-layup moulding technique is used for the composite fabrication. Natural coir fiber and synthetic fevicol adhesive are used as reinforcement and matrix phase materials respectively. Initially the tensile and impact strength of the coir fiber biocomposite laminate is determined and then a helmet is fabricated to protect the head of the children from injuries as a product of biocomposite.